FAST FOOD AND ITS IMPACT ON STUDENT HEALTH - Aisyah Azzahra Harahap; Azqiya Niswah Rofilah; Fachri Anandyto Thiagarajah; Risqi Arief Purba; Aisyah Putri Ramadhani Harahap; Sri Widayati M.A (MEDALION Journal: Medical Research, Nursing, Health and Midwife Participation, 2025)
This study analyzes the phenomenon of fast food consumption and its impact on students' health in Indonesia. Using a qualitative approach with literature study method, this research examines the characteristics of fast food, driving factors for consumption, and resulting health implications. The results indicate that fast food has strong appeal for students due to its practicality, affordable price, and modern image. However, excessive consumption leads to various health problems such as obesity, diabetes, hypertension, and other degenerative diseases. These findings underscore the urgency of nutritional education and structured interventions to establish healthy consumption patterns among students.